Biosystematic approach to geographic variations of house mouse group, Mus musculus L.1766 - J. Darvish (Iranian Journal of Animal Biosystematics, 2008)
The matrix of qualitative and quantitative data compiled from comparative measures of 14 dental and skull morphology and 17 dentally variable morphometric characters taken from samples of 18 populations of house mouse, Mus musculus, which were previously determined genetically, distributed over Eurasian and north African habitats of the species are used for uni-and-multivariate analysis, aiming to clarify and settle the status of taxonomy, and hence, biosystematic and phylogography of these populations. The genetic attributes, already worked on, are used simultaneously to check against, match, compare and analyze with those of morphology and morphometry. Efforts have been made to approach the geographic inter- and- intraspecies and population variations of house mouse, focusing on subspecies status or category.